1987
DOI: 10.1021/bi00396a015
|View full text |Cite
|
Sign up to set email alerts
|

Calcium binding domains and calcium-induced conformational transition of SPARC/BM-40/osteonectin, an extracellular glycoprotein expressed in mineralized and nonmineralized tissues

Abstract: SPARC, BM-40, and osteonectin are identical or very closely related extracellular proteins of apparent Mr 43,000 (Mr 33,000 predicted from sequence). They were originally isolated from parietal endoderm cells, basement membrane producing tumors, and bone, respectively, but are rather widely distributed in various tissues. In view of the calcium binding activity reported for osteonectin, we analyzed the SPARC sequence and found two putative calcium binding domains. One is an N-terminal acidic region with cluste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
151
0

Year Published

1989
1989
2004
2004

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 206 publications
(159 citation statements)
references
References 58 publications
8
151
0
Order By: Relevance
“…Several extracellular ligands have been identified for BM-40 including some collagen types and cytokines (1). This indicated various binding sites on BM-40 in agreement with a previous proposal of a mosaic structure for the protein (2). The most recent interpretation of the domain structure based on recombinant deletion mutants and a crystal structure of a fragment encompassing the C-terminal 150 residues (3,4) demonstrated an acidic and flexible N-terminal domain I (ϳ50 residues) followed by a follistatin-like (FS) 1 module (ϳ75 residues) and a novel extracellular calcium-binding (EC) module (ϳ150 residues).…”
supporting
confidence: 88%
See 1 more Smart Citation
“…Several extracellular ligands have been identified for BM-40 including some collagen types and cytokines (1). This indicated various binding sites on BM-40 in agreement with a previous proposal of a mosaic structure for the protein (2). The most recent interpretation of the domain structure based on recombinant deletion mutants and a crystal structure of a fragment encompassing the C-terminal 150 residues (3,4) demonstrated an acidic and flexible N-terminal domain I (ϳ50 residues) followed by a follistatin-like (FS) 1 module (ϳ75 residues) and a novel extracellular calcium-binding (EC) module (ϳ150 residues).…”
supporting
confidence: 88%
“…The insert was then restricted with NheI and XhoI and cloned into the episomal expression vector pCEP-Sh (25) that contained the puromycin instead of the phleomycin resistance gene. 2 The correctness of the insert was verified by DNA cycle sequencing. Transfection of human EBNA-293 cells (Invitrogen) and purification of the recombinant mutant followed established protocols (3,25).…”
Section: Sources Of Extracellular Matrix Ligands and Proteases-mentioning
confidence: 99%
“…Studies with BM-40 demonstrated 25 -30% a-helical conformation, which was distinctly reduced after removal of calcium [147]. The data also indicated the cooperative binding of up to seven calcium ions which is close to the nine binding sites predicted from the sequence.…”
Section: Bm-40/osteonectinisparcmentioning
confidence: 53%
“…Reproduced with permission from [40] before considered to be a bone-specific protein with binding activities for calcium, hydroxyapatite and collagen I [I 511. Sequence data [40,41,147] indicates that the protein consists of four domains I -IV (Fig. 7) and that the two terminal domains (I, IV) represent potential calcium-binding sites.…”
Section: Bm-40/osteonectinisparcmentioning
confidence: 99%
See 1 more Smart Citation